(untitled) (Quinto Sol, 2019)
Until a few decades ago the writing of texts in Mapuzungun language by Mapuche speakers has been considered an exception. Nevertheless, the recovery of records in several archives, which is lately taking place, allows to modify this conceptualization and to consider textualizations that were produced at the intersection of written and oral registers. In this article we analyze from this perspective the productions in Mapuzungun language made by Nahuelpi, who methodically interacted in the early years of the twentieth century with the German anthropologist Roberto Lehmann-Nitsche in the city of La Plata, Argentina. We examine the literacy events in which Nahuelpi’s documentary and writing activities were developed in order to consider the construction of his investigative role, clues of his participation in those events, and the technological dimension of his practice.